Antibodies against conserved amidated neuropeptide epitopes enrich the comparative neurobiology toolbox - Conzelmann Markus; Jékely Gáspár (EvoDevo, 2012)
Abstract Background Neuronal antibodies that show immunoreactivity across a broad range of species are important tools for comparative neuroanatomy. Nonetheless, the current antibody repertoire for non-model invertebrates is limited. Currently, only antibodies against the neuropeptide RFamide and the monoamine transmitter serotonin are extensively used. These antibodies label respective neuron-populations and their axons and dendrites in a large number of species across various animal phyla. Results Several other neuropeptides also have a broad phyletic distribution among invertebrates, including DLamides, FVamides, FLamides, GWamides and RYamides. These neuropeptides show strong conservation of the two carboxy-terminal amino acids and are α-amidated at their C-termini. We generated and affinity-purified specific polyclonal antibodies against each of these conserved amidated dipeptide motifs. We thoroughly tested antibody reactivity and specificity both by peptide pre-incubation experiments and by showing a close correlation between the immunostaining signals and mRNA expression patterns of the respective precursor genes in the annelid Platynereis. We also demonstrated the usefulness of these antibodies by performing immunostainings on a broad range of invertebrate species, including cnidarians, annelids, molluscs, a bryozoan, and a crustacean. In all species, the antibodies label distinct neuronal populations and their axonal projections. In the ciliated larvae of cnidarians, annelids, molluscs and bryozoans, a subset of antibodies reveal peptidergic innervation of locomotor cilia. Conclusions We developed five specific cross-species-reactive antibodies recognizing conserved two-amino-acid amidated neuropeptide epitopes. These antibodies allow specific labelling of peptidergic neurons and their projections in a broad range of invertebrates. Our comparative survey across several marine phyla demonstrates a broad occurrence of peptidergic innervation of larval ciliary bands, suggesting a general role of these neuropeptides in the regulation of ciliary swimming.